Impact-Echo Testing Methods for Determining the Defect of Cured-In-Place Pipe - Houssam Mahmoud; Lubos Pazdera (e-Journal of Nondestructive Testing)
Non-destructive testing of cured-in-place pipe (CIPP) ensures that the liner (CIPP) has been successfully installed and that the pipe will function reliably, the Acoustic methods are used to detect cracks or leaks in pipes as the Impact-Echo (IE) method. This study aims to design a device to carry the tools inside the pipe. The received signals were analyzed to identify delamination, cavities behind CIPP, and overall pipe health.